Seismic analysis of an ancient masonry palace through two simplified numerical methods. (10th November 2022) - Scuro, Carmelo; Olivito, Renato Sante; Lamonaca, Francesco; Carnì, Domenico Luca; Angotti, Cinzia
The aim of the paper is to study the reliability of simplified numerical models (SNMs) for seismic structural assessment identification accuracy. The advantages of using SNMs with respect to the traditional finite element approaches come from their commercial availability, the structural templates already implemented, and the reduced computational burden that allow the evaluation of the seismic structural assessment in some minutes instead of days. But the drawback to using SNMs alone in the study of large-scale structures is the crude accuracy justified by the simplifications they assume. This study is conducted on an actual case: the Trentacapilli palace (Bisignano, Calabria, Italy). This palace was chosen because it is subjected to foundation subsidence and includes different structural elements, allowing different kinds of SNMs to be used.